Effect of Successive Multiple Doping of La, Nb and Fe on Structure and Lattice Vibration of MPB PZT. (2018) - Samanta, Shibnath; Sankaranarayanan, V.; Sethupathi, K.
Abstract: Morphotropic phase boundary (MPB) Lead zirconate titanate [i.e Pb(Zr0.52 Ti0.48 )O3, PZT] is modified by incorporation of i) La in Pb-site, ii) simultaneously La in Pb-site and Nb in Zr/Ti site and iii) simultaneously La in Pb-site, Nb and Fe in Zr/Ti-site. Samples are prepared by alkoxide sol-gel synthesis. XRD study reveals peak shift towards lower 2θ upon La addition but the shift is towards higher 2θ for both La and Nb are incorporated. Addition of Fe makes peak shift towards higher angle but the amount of shift is very small with respect to that of La and Nb doping. The XRD data is further analyzed with the help of Rietveld refinement which reveals change in lattice parameters. It is observed that successive doping of La, La-Nb and La-Nb-Fe decrease both lattice parameters a and c. However, for the case of Nb and La co-doped PZT the value of c increases with respect to the c of only La doped PZT. The charge difference in Nb (5+) and Fe (3+) ions have compensating effect as they are doped in the same atomic site (i.e. B-site of the ABO3 ) which is having charge 4+. Raman spectroscopic study reveals more complex effect of successive multiple doping of La, Nb and Fe. Some of the observations in Raman spectroscopy are supportive to the observations made in XRD. Raman spectra are analyzed by cumulative fitting of de-convoluted peaks, which represent various individual vibrational modes: reveal changes happening in the lattice due to the systematic successive doping of La, Nb and Fe.